A finite element analysis on hybrid UHMWPE pads of a spherical bearing. (November 2015) - Peng, X.; Wu, C. L.; Chen, Z. H.
Abstract : The contact surface of a heavily loaded spherical bearing consists of a steel convex element and hybrid ultra-high molecular weight PE pads fixed to a rigid concave element, to reduce the maximum contact stress. In present paper, finite element analysis simulations on models of different contact surfaces are carried out, to study on problems including the influence of polymer pads on the contact stress of the spherical bearing, the material and the distribution of pads etc. Significant stress concentration appears on the rigid spherical contact surface. The concentration can be relieved by the use of elastic pads. The appropriate distribution and quantity of pads can also reduce the maximum contact stress. An analysis of the composite structure polymer pad shows that the actual contact factor increases with the growth of forces on the contact surface, and the carbon ring is the major loaded component.